Exploring the Impact of Bending on Circularly Polarized Textile Reconfigurable Antenna - Sandeep, D. Ram; Salma, S.; Madhav, B.T.P (2024 IEEE Wireless Antenna and Microwave Symposium (WAMS), 2024)
This investigation delves into the impact of bending on a versatile, frequency-adjustable textile antenna. This antenna achieves four distinct configurations by leveraging two BAR-64-03W pin diodes. In standalone conditions, In C1 mode it resonates at various frequencies of 2.4, 4.29, 5.78, and 9.39; in C2 it function at 5 and 5.9; in C3 it operates at 4.4 and 5.8 in C3; and in C4 it resonates at 3.5, 4.4, 5.3. CP occurs at frequencies of 2.4, 3.5, 5.8, and 5.9 GHz within these specified setups. The structural changes induced by bending disrupt the antenna's functionality, prompting an extensive exploration of its electromagnetic behavior variations. Assessing both vertical and horizontal bending effects across these configurations reveals a maximum frequency deviation of 0.35 GHz. Concurrent shifts in axial ratios are also observed. The analyses highlight the antenna's robust performance under diverse human body curvature scenarios.